2015
DOI: 10.1111/jam.12852
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of fungal populations in corn silage conserved under polyethylene or biodegradable films

Abstract: Even if the new MB plastic film did not completely maintain the anaerobiosis in the upper layer of silage, the overall silage quality was not compromised and was similar to that observed under PE, indicating that the development and use of MB film to cover silage is promising, but needs some improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 42 publications
2
21
0
2
Order By: Relevance
“…Keller et al (2013) found A. flavus as the predominant Aspergillus species at both ensiling and at silo opening in Brazil, and El-Shanawany et al (2005), in a farm survey, found A. flavus as the dominant species in corn silage in Egypt. On the other hand, Garon et al (2006) and Spadaro et al (2015) did not find A. flavus in corn silage in the temperate climates of France or northern Italy, but instead reported the presence of A. parasiticus and A. fumigatus. However, Richard et al (2007) detected A. flavus in farm corn silage in France after 11 mo of conservation.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Keller et al (2013) found A. flavus as the predominant Aspergillus species at both ensiling and at silo opening in Brazil, and El-Shanawany et al (2005), in a farm survey, found A. flavus as the dominant species in corn silage in Egypt. On the other hand, Garon et al (2006) and Spadaro et al (2015) did not find A. flavus in corn silage in the temperate climates of France or northern Italy, but instead reported the presence of A. parasiticus and A. fumigatus. However, Richard et al (2007) detected A. flavus in farm corn silage in France after 11 mo of conservation.…”
Section: Discussionmentioning
confidence: 86%
“…Mycotoxins are secondary metabolites with low molecular weight that are mainly produced by fungi belonging to the Aspergillus, Penicillium, Fusarium, and Alternaria genera . Mold and mycotoxin contamination of several feed and forages represent an important problem for human and animal health (Driehuis, 2013;Spadaro et al, 2015). Furthermore, this contamination causes increases in food production costs as a result of the increased need for testing, lower prices received for contaminated loads, potential lawsuits from consumers, and decreased livestock performance (Mitchell et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The major common feature shared by the two substrates was the high temperature during fermentation, which led to a selection of thermo‐tolerant microorganisms. A. fumigatus is able to grow at temperatures that approach the upper limit for eukaryotes, thanks to unique mechanisms of stress resistance, useful to bypass high‐temperature processes and starting a re‐colonization of the substrate in the absence of competition with other microbial species . This mechanism is particularly evident analysing A. fumigatus abundance in corn silage stored anaerobically for 270 days when the silo was opened and the material exposed to air.…”
Section: Discussionmentioning
confidence: 99%
“…A. fumigatus is able to grow at temperatures that approach the upper limit for eukaryotes, thanks to unique mechanisms of stress resistance, useful to bypass high-temperature processes and starting a re-colonization of the substrate in the absence of competition with other microbial species. 49 This mechanism is particularly evident analysing A. fumigatus abundance in corn silage stored anaerobically for 270 days when the silo was opened and the material exposed to air. Starting from a concentration close to the detection limit (100 cfu/g) immediately after opening, A. fumigatus abundance increased rapidly reaching the highest concentrations ever detected in an organic substrate (7.4 × 10 4 to 2.35 × 10 7 cfu/g).…”
Section: Discussionmentioning
confidence: 99%
“…The biomass collected with higher moisture occupies more volume and, for that reason, it is more expensive to collect, store and transport [141]. Furthermore, stover harvested with high humidity allows the presence of moldy and saprophytic fungi, facilitating their rapid decomposition and, consequently, bringing about economic losses [142]. Thus, it could be imperative to dry the biomass prior to transport to the site of its conversion, although this increases the economic cost and decreases the net energy obtained because some energy has to be spent in drying the biomass.…”
Section: Dual Purpose Crops Optimized For Grain-biomass Productionmentioning
confidence: 99%